AS PERSPECTIVAS DO OMNICHANNEL FRENTE À COMUNICAÇÃO INTEGRADA DE MARKETING - FAGUNDES, LIGIA (2018)
The goal of this research has been raised from questionings about sociocultural aspects and their associations with a modern consumption way and its results in several societal aspects, besides, aspect dimensions under technology influence and its exponential impacts. Emerges then, the research object analysis as a potential protagonist mainly in retail and 21st century communications. Omnichannel term (omni + channel) relates to sales product and services activities involved in distribution through multiple channels. This research will discuss the Omnichannel approach over trading and multichannel communication impact, as an alternative from consumer search in making part of product and solution launches, reducing distances between corporations and customers, moreover to promote experiences either in online the stores sites. Results expected from this research lie on integrated marketing communications management in Omnichannel environment and its challenges in such integration process. The methodology used was descriptive-exploratory analysis in a qualitative field research among Omnichannel market executives